A Survey on perceived speaker traits: Personality, likability, pathology, and the first challenge. (January 2015) - Schuller, Björn; Steidl, Stefan; Batliner, Anton; Nöth, Elmar; Vinciarelli, Alessandro; Burkhardt, Felix; van Son, Rob; Weninger, Felix; Eyben, Florian; Bocklet, Tobias; Mohammadi, Gelareh; Weiss, Benjamin
Abstract: The INTERSPEECH 2012 Speaker Trait Challenge aimed at a unified test-bed for perceived speaker traits – the first challenge of this kind: personality in the five OCEAN personality dimensions, likability of speakers, and intelligibility of pathologic speakers. In the present article, we give a brief overview of the state-of-the-art in these three fields of research and describe the three sub-challenges in terms of the challenge conditions, the baseline results provided by the organisers, and a new openSMILE feature set, which has been used for computing the baselines and which has been provided to the participants. Furthermore, we summarise the approaches and the results presented by the participants to show the various techniques that are currently applied to solve these classification tasks.